Vitamins, minerals, essential fatty acids and colorectal cancer risk in the United Kingdom Dietary Cohort Consortium. - Key, T; Appleby, P; Masset, G; Brunner, E; Cade, J; Greenwood, D; Stephen, A; Kuh, D; Bhaniani, A; Powell, N; Khaw, K (2012)
The risk for colorectal cancer may be influenced by the dietary intake of various vitamins, minerals and essential fatty acids. We conducted a pooled analysis of dietary data collected using food diaries in seven prospective studies in the United Kingdom Dietary Cohort Consortium. Five hundred sixty-five cases of colorectal cancer were matched with 1,951 controls on study centre, age, sex and recruitment date. Dietary intakes of retinol, vitamin A, thiamin, riboflavin, vitamin B6, folate, vitamin B12, vitamin D, calcium, iron, magnesium, potassium, n - 6 fatty acids, n - 3 fatty acids and the ratio of n - 6 to n - 3 fatty acids were estimated and their associations with colorectal cancer examined using conditional logistic regression models, adjusting for exact age, height, weight, energy intake, alcohol intake, fiber intake, smoking, education, social class and physical activity. There were no statistically significant associations between colorectal cancer risk and dietary intake of any of the vitamins, minerals or essential fatty acids examined.